Art on the rocks : more than 35 colorful & contemporary rock-painting projects, tips, and techniques to inspire your creativity! /: more than 35 colorful & contemporary rock-painting projects, tips, and techniques to inspire your creativity!. (2017) - Bac, F. Sehnaz; Redondo, Marisa; Vance, Margaret
No abstract available